2004
DOI: 10.1089/1092875041358476
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Aerosol Dynamics Model with Gas/Particle Transport and Modal Approach

Abstract: A multicomponent aerosol dynamic model, that is suitable for regional/global chemical transport models, was developed by combining a thermodynamic module and a modal approach module and by using a dynamic gas/aerosol relationship. The modal approach, which represents the particle size distribution as the superposition of three log-normal size distributions without any assumption on the characteristics of the log-normal distribution, was introduced for simulating the evolution of the chemical species of aerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In this study, we focused primarily on the influence of water solubility on the optical properties of polydispersed aerosols and the role of WSOC on light-absorbing optical properties. We developed a size-resolved model for calculating the optical properties of organic aerosols by combining thermodynamic hygroscopic growth and aerosol dynamics models (Jung et al, 2004). Then, we applied the model to the aerosol measurement data at a megacity in northeast Asia, Seoul.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused primarily on the influence of water solubility on the optical properties of polydispersed aerosols and the role of WSOC on light-absorbing optical properties. We developed a size-resolved model for calculating the optical properties of organic aerosols by combining thermodynamic hygroscopic growth and aerosol dynamics models (Jung et al, 2004). Then, we applied the model to the aerosol measurement data at a megacity in northeast Asia, Seoul.…”
Section: Introductionmentioning
confidence: 99%
“…Modal algorithms that represent the aerosol size distribution as the sum of several lognormal distributions, each characterized by a number concentration, median diameter, and geometric standard deviation, have been developed by Herzog et al (2004), Jung et al (2004) and Vignati et al (2004) and implemented in Easter et al (2004), Ghan et al (2001), Stier et al (2005) and Wilson et al (2001) in global models. Except for Jung et al (2004), the versions of the modal approach cited here have prescribed constant values to the geometric standard deviations such that only two of the three lognormal parameters are predicted variables. Zhang et al (1999) demonstrated that allowing the geometric standard deviation to vary results in greater accuracy under some conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The aerosol optical properties depend on size distribution and refractive index of the chemical composition, which means that the mass concentration alone is not sufficient to determine the aerosol extinction coefficient. This study simulated the aerosol optical properties by using polydispersed aerosol thermodynamic model and the optical properties were calculated using Mie theory [2,8,12]. Finally, the optical properties thus obtained were compared with the AERONET AOT measurement data.…”
Section: Discussionmentioning
confidence: 99%